DEVELOPMENT OF SNAKES AND LADDERS MEDIA TO TEACH WRITING SKILL ON DESCRIPTIVE TEXT FOR JUNIOR HIGH SCHOOL - Saputri, Malinda Puji; Rofi'ah, Siti; Widi, Widiarini; Saifudin, Ahmad (Jurnal Pembelajaran dan Ilmu Pendidikan, 2025)
This study aims to develop Snakes and ladders game media to teach writing skills in grade VII students of MTs Syekh Subakir 2. Based on the need analysis with an English teacher, it was stated that during the pandemic students had difficulty understanding English material. The results of the questionnaire 10 students also stated that learning English was difficult, especially writing. This study and development proposed the (Borg, W. R. and Gall, 1989). Data was collected using interviews and questionnaire The process of developing Snakes and ladders learning media is carried out in 8 stages, namely: (1) Potential and problems, (2) Data collection, (3) Product design, (4) Design validation, (5) Design revision, ( 6) Product testing, (7) Usage trial (8) product revision. The result of Snakes and ladders media validated by material experts obtained material experts 86.67% and from obtained media experts 90% which means that it is valid and feasible for use as learning. Furthermore, this can be proven by the analysis of student satisfaction questionnaires which are used as a reference for the feasibility of learning products. The results of the data showed 100%, which stated that students were greatly helped and became more active writing with the Snakes and ladders learning media. In conclusion, Snakes and ladders media that was developed can use to teach writing in MTs Syekh Subakir 2.